Analysis of the current state of the problem of compositional devices constructive sets of uniforms for railway workers of Ukraine - Prikhodko-Kononenko, I.; Kolosnichenko, E.; Ostapenko, N.; Kolosnichenko, M. (Theory and practice of design, 2015)
The article described the current uniforms for railway workers of Ukraine. On the basis of theoretical studies are organized by compositional and structural features varieties of sets of uniforms for men and women for the conductor rail. Found insufficient quality ergonomic, aesthetic and reliability, formulated the task of developing assortment series sets with improved quality.